(untitled) (Journal of Human Sciences, 2025)
There is no doubt that the policy of the British administration in Tripoli and Cyrenaica had far-reaching effects that affected all aspects of life, and perhaps the most important of them were the economic aspects. Therefore, this study entitled “The Economic Policy of the British Administration in Tripoli and Cyrenaica "1943-1949" came to shed light on that aspect. The study begins with the political implications. These conditions affected the population after the end of World War II, following the measures taken by the British administration in Tripoli and Cyrenaica. The studyalso addresses aspects of economic life in the region, such as agriculture, some agricultural products, trade and industry, monetary policy, banks and foreign companies. Besides that, knowing the extent to which aspects were affected by the policy of the British administration in Tripoli and Cyrenaica and also knowing the developments that occurred in these aspects. The study reached the conclusion that the military administration was not serious in addressing the bad economic situation in the region of Tripoli and Cyrenaica. The purpose behind that it is a justification and guarantee for the continuation of its occupation of the country. It became clear when the issue of Libya’s independence was raised at the United Nations and the colonial powers: Britain, France and Italy demanded continuing its guardianship over it under the pretext that its economic conditions do not enable it to gain its independence.